Surdos professores: a constituição de identidades por meio de novas categorias pelo trabalho em territórios educativos - Cunha Júnior, Elias Paulino da (2022)
This work is organized as a theoretical discussion about the reality of Deaf teachers in the current context. It focuses on a theorization on the constitution of these workers from the bias of Applied Linguistics. In this sense, the perspective of dialectics in Marx (1857, 1858, 2011) and Engels (1974) (thesis, antithesis, synthesis), transported to the methodology of our production, in scientific rigor, will give a better understanding of the teacher profile. Thus, thesis, understood as the educational practice from the listener's perspective in what is already established as the ideal model to be followed, both in the social, cultural, economic, political aspect, as well as in the mentality linked to the conditions of the educational reality and in academic productions; antithesis, as a divergence, of what is posed by the bias of hearing teachers, in contradiction with the cultural and linguistic reality of Deaf teachers, for readjustment and change of mentality through clash and modulations in the relations of productions of educational processes, above all, to to seek new paths, and, in synthesis, the urgency of legitimizing a new category of workers of recognition in educational loci, in overcoming the initial thesis. We understand that this methodology supports our justifications for reflective procedures to enable relevant relationships with Applied Linguistics. This achievement recovers concepts about: Territory, Borders, Spaces, Place, Mobility, to defend the situation of Deaf teachers. In addition, it makes use of the concepts of Identity, to defend the Identities of Deaf teachers not as modulations, but as evidence. as a category of Deaf@s Teachers for the legitimacy of educational work. Finally, it recovers the concepts that involve the linguistic process: Monoglossia; Heteroglossia; Bilingualism; Diglossia; Additional Language; Multilingualism; Translanguage and Linguistic Repertoire. So also the Pedagogical Process: Literacy; Literacy; Multiliteracies; Multimodality; Multiculturalism; Additional Pedagogical Language and Pedagogical Repertoire. The role of the constitution of these Individuals/Subjects, Deaf Teachers, embodied in Pedagogical Context(s) and in Linguistic Identity, is explained through the apparatus of meaning and impacts on the ways they were/are, historically, marginalized. Therefore, this work points out paths for an analysis of the contexts of action of Deaf Teachers and the ways in which their practices can be interpreted